2021
DOI: 10.1007/s42421-021-00039-y
|View full text |Cite
|
Sign up to set email alerts
|

A Proactive Approach to Evaluating Intersection Safety Using Hard-Braking Data

Abstract: Typical safety improvements at signalized intersections are identified and prioritized using crash data over 3–5 years. Enhanced probe data that provides date, time, heading, and location of hard-braking events has recently become available to agencies. In a typical month, over six million hard-braking events are logged in the state of Indiana. This study compared rear-end crash data over a period of 4.5 years at 8 signalized intersections with weekday hard-braking data from July 2019. Using Spearman’s rank-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The objective of this study is to determine if lane width measurements from sensors onboard production vehicles can be used to screen public road networks for sections that have less than prescribed lane widths. Previous studies have found many uses for connected vehicle data, including pavement marking evaluation, traffic signal performance, and crash mitigation through surrogate safety measures and hard braking [ 17 , 18 , 19 , 20 , 21 ]. The benefit of using production vehicle data is that it can be crowdsourced and provide ubiquitous coverage across the state without resource-intensive deployments and data collection.…”
Section: Objectivementioning
confidence: 99%
“…The objective of this study is to determine if lane width measurements from sensors onboard production vehicles can be used to screen public road networks for sections that have less than prescribed lane widths. Previous studies have found many uses for connected vehicle data, including pavement marking evaluation, traffic signal performance, and crash mitigation through surrogate safety measures and hard braking [ 17 , 18 , 19 , 20 , 21 ]. The benefit of using production vehicle data is that it can be crowdsourced and provide ubiquitous coverage across the state without resource-intensive deployments and data collection.…”
Section: Objectivementioning
confidence: 99%
“…A study conducted on 23 construction work zones that covered approximately 150 centerline miles of Indiana interstate roadway in the summer of 2019, found that there was approximately 1 crash for every 147 hard-braking events in and around a construction site with an R 2 value of 0.85 [23]. Thus, the new commercially available hard-braking data sources provide an opportunity for agencies to follow up with mitigation measures addressing emerging problems much quicker than typical practices that rely on 3 -5 years of crash data [24]. This study presents a methodology using these hard-braking events as a surrogate for crash incidents for impact evaluation of queue warning trucks and digital alerts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the emergence and improvement of commercially available connected vehicle (CV) data, new techniques have been developed to assess operational and safety performance at intersections without the need for costly infrastructure investments. CV hard-braking events have been proven to be a surrogate of crashes [18]. Vehicle trajectories have been used to estimate queue lengths [19] [20].…”
Section: Literature Reviewmentioning
confidence: 99%